Throughput and delay analysis for IEEE 802.11 multi-hop networks considering data rate - Kanematsu, Takeshi; Sanada, Kosuke; Li, Zhetao; Pei, Tingrui; Choi, Young June; Nguyen, Kien; Sekiya, Hiroo (International Journal of Distributed Sensor Networks, 2020)
In an IEEE 802.11 Distributed Coordination Function–based wireless network with multiple hops, a node operates on its own with several predefined data rates (i.e. following modulation and coding schemes). Moreover, the IEEE 802.11 Distributed Coordination Function node’s communication is characterized by transmission and carrier-sensing distances. The transmission one is, in general, reverse proportional to the data rate. Meanwhile, the carrier distance keeps constant regardless of the modulation and coding scheme. Therefore, when a node has a high transmission rate, within its carrier-sensing range, the number of nodes may increase. The previous works have not yet extensively investigated the impact of data rates on such a scenario. This article addresses that issue aiming to quantify the network performance of the multi-hop IEEE 802.11 networks. As a solution, we propose the mathematical expressions, which consider data rates, for end-to-end throughputs, as well as delays in the network with string topology. We confirm the expressions’ correctness by presenting the quantitative agreements between the analytical and simulation results.
Keywords: End-to-end throughput; High transmission rate; Ieee 802.11 distributed coordination functions; IEEE 802.11 networks; Mathematical expressions; Modulation and coding schemes; Multihop networks; Quantitative agreement; carrier-sensing; data rate; delay; Multi-hop networks; performance analysis; throughput